2012
DOI: 10.1136/annrheumdis-2012-202357
|View full text |Cite
|
Sign up to set email alerts
|

Implication of IL-2/IL-21 region in systemic sclerosis genetic susceptibility

Abstract: Objective The interleukin 2 (IL-2) and interleukin 21 (IL-21) locus at chromosome 4q27 has been associated with several autoimmune diseases, and both genes are related to immune system functions. The aim of this study was to evaluate the role of the IL-2/IL-21 locus in systemic sclerosis (SSc). Patients and methods The case control study included 4493 SSc Caucasian patients and 5856 healthy controls from eight Caucasian populations (Spain, Germany, The Netherlands, USA, Italy, Sweden, UK and Norway). Four si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…The results showed that allelic combination (haplotype) consisting of rs2069762A-rs6822844T-rs6835457G-rs907715T was associated with systemic sclerosis and limited cutaneous systemic sclerosis subtype. 42 An association between IL2 and IgE-mediated allergy, asthma, and atopic eczema, has been mapped to the IL2 gene (but not IL15). Using 235 families to study the genetic predisposition to these diseases, two SNPs in the IL2 gene were found significantly linked, and one of them (rs2069762), located in the IL2 promoter, influences the level of IL-2 expression.…”
Section: Association With Diseasesmentioning
confidence: 99%
“…The results showed that allelic combination (haplotype) consisting of rs2069762A-rs6822844T-rs6835457G-rs907715T was associated with systemic sclerosis and limited cutaneous systemic sclerosis subtype. 42 An association between IL2 and IgE-mediated allergy, asthma, and atopic eczema, has been mapped to the IL2 gene (but not IL15). Using 235 families to study the genetic predisposition to these diseases, two SNPs in the IL2 gene were found significantly linked, and one of them (rs2069762), located in the IL2 promoter, influences the level of IL-2 expression.…”
Section: Association With Diseasesmentioning
confidence: 99%
“…(3) genotype frequencies in cases and controls were both available for estimating an odds ratios (OR) and their 95% confidence interval (CI); (4) studies that included ADs that were diagnosed according to the respective classification criteria [6][7][8][9][21][22][23][24][25]; (5) the papers should be published with full-text articles. The exclusion criteria included: (1) studies that contained overlapping data with other literatures;…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Genotype distributions of the SNPs in the control groups were consistent with HWE, with the exception of one study [24]. The ethnicities encompassed in qualified studies were stratified into Caucasian, African-American, and Asian populations [6][7][8][9][21][22][23][24][25]. The ADs studied in the articles included SLE [6,21,22], GD [8,24], HT [24], RA [7,23], SSc [9], and Uveitis [25].…”
Section: Eligible Studiesmentioning
confidence: 99%
See 2 more Smart Citations